2008
DOI: 10.1074/jbc.m707803200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for the Activation of Escherichia coli CTP Synthase by the Allosteric Effector GTP Are Stringent, but Requirements for Inhibition Are Lax

Abstract: Cytidine 5-triphosphate synthase catalyzes the ATPdependent formation of CTP from UTP using either NH 3 or L-glutamine (Gln) as the source of nitrogen. GTP acts as an allosteric effector promoting Gln hydrolysis but inhibiting Glndependent CTP formation at concentrations of >0.15 mM and NH 3 -dependent CTP formation at all concentrations. A structure-activity study using a variety of GTP and guanosine analogues revealed that only a few GTP analogues were capable of activating Gln-dependent CTP formation to var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…19,22,39,44 As previously observed, 19 the S 0.5 values of ATP and UTP are interdependent (Table 1). At subsaturating ATP concentration (150 μ M), the S 0.5 of UTP increased to 200 μ M, while at 60 μ M UTP, the ATP S 0.5 value increased to 330 μ M. Interestingly, we found that lowering the GTP concentration from the optimal (200 μ M) to its EC 50 (50 μ M) also reduced the ATP S 0.5 value to 81 ± 5 μ M ( n = 5).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…19,22,39,44 As previously observed, 19 the S 0.5 values of ATP and UTP are interdependent (Table 1). At subsaturating ATP concentration (150 μ M), the S 0.5 of UTP increased to 200 μ M, while at 60 μ M UTP, the ATP S 0.5 value increased to 330 μ M. Interestingly, we found that lowering the GTP concentration from the optimal (200 μ M) to its EC 50 (50 μ M) also reduced the ATP S 0.5 value to 81 ± 5 μ M ( n = 5).…”
Section: Resultssupporting
confidence: 64%
“…Indeed, NADH inhibition resembles that of guanosine and other purines. 44,53 Like guanosine, NADH inhibits ammoniadependent synthesis (Figure S6) and similarly shifts both GTP activation and inhibition curves 10,44 (Figure 6e, compare to Figure 4 in ref 44). Potentiation of GTP dual effects is diagnostic for mutual and nonexclusive binding in noncooperative systems.…”
Section: Discussionmentioning
confidence: 76%
“…GTP was reported earlier as an activator of CTPS enzymes from E. coli (Lunn et al ., ; Barry et al ., ). Indeed, also the CTPS3 protein from Arabidopsis revealed markedly increased activity in the presence of GTP.…”
Section: Resultsmentioning
confidence: 98%
“…6.3.4.2). [6,2227] All four enzymes were expressed and purified as described in our previous work. [28] …”
mentioning
confidence: 99%